Implementasi Nilai Muatan Lokal dalam Pembelajaran Seni Budaya di SD Negeri Pucangsewu Pacitan - Christina Oktivida Ardhani; Moh. Fathurrahman (Pusdikra Publishing, 2026)
This study aims to analyze the implementation of local content values in Cultural Arts learning at SD Negeri Pucangsewu. The research is grounded in the growing concern regarding the declining awareness of local cultural identity among elementary students due to globalization. Cultural arts learning offers a strategic space to integrate local wisdom as part of character education and contextual learning. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, Cultural Arts teacher, and students. Data analysis followed the interactive model of reduction, display, and conclusion drawing. The findings reveal that local cultural elements such as Kethek Ogleng, Wayang Beber, Ronthek, and the traditional ritual Ceprotan are integrated through contextual lesson planning, practical artistic activities, project-based assignments, and reflective discussions on cultural values. The implementation enhances students’ participation, cultural literacy, collaborative skills, and sense of regional identity. The novelty of this study lies in demonstrating how structured integration of Pacitan’s local culture within formal Cultural Arts learning contributes to character education and supports the realization of culturally responsive pedagogy at the elementary level.